Clinical features of oral cavity of patients with non-Hodgkin’s lymphoma undergoing chemotherapy - Suroso, Diptakanya Murdi; Dewi, Tenny Setiani; Fadjari, Trinugroho Heri (Universitas Padjadjaran, 2013)
Introduction: Non-Hodgkin`s lymphoma is one of hematologic malignancy that responds to chemotherapy. Chemotherapy agent can cause oral complication such as oral mucositis, hemorrhage, xerostomia, hyposalivation and periodontitist. The purpose of this study is to determine the clinical feature of the oral cavity in patients with non-Hodgkin`s lymphoma whose underwent chemotherapy Method: This study used an observational descriptive method. This type of research is observational descriptive. The study population was non-Hodgkin’s lymphoma sufferers who were undergoing chemotherapy at the Hematology and Medical Oncology Outpatient Installation Division of Internal Medicine at Hasan Sadikin Hospital Bandung. The study sample was taken by consecutive sampling method The numbers of samples in this study were 30 people according to predetermined criteria. Result: The result shows that all samples have abnormalities of the oral cavity that patients who have an abnormality are amounted to 20% and patients who have more than one kind of oral abnormalities amounted to 80%. An abnormality of the oral cavity that the most often found in this study is xerostomia with hyposalivation. Conclusion: Clinical feature of the oral cavity in patients with non-Hodgkin`s lymphoma whose underwent chemotherapy are abnormalities in the oral cavity, where the number of samples that experienced more than one type of oral cavity abnormality was greater when compared to the number of samples with a kind of abnormality. Oral cavity. Most of the samples studied had oral cavity abnormalities in the form of serostomia accompanied by hyposalivation.